Characterisation of Membrane Glycoproteins that are Essential for Flagellar Attachment in the Bloodstream Form of Trypanosoma brucei - MCATEER, LOUISE (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
The African trypanosome, Trypanosoma brucei, is a unicellular parasitic protist that causes a severe disease, trypanosomiasis, in humans and livestock in sub-Saharan Africa. The trypanosome has a single flagellum that performs important roles in motility, environmental sensing and immune evasion. Unusually, the flagellum is attached laterally along the outer surface of the parasite by a complex membrane junction called the flagellar attachment zone (FAZ). Flagellar attachment is essential for proliferation of the bloodstream form of the trypanosome because the FAZ provides the positional information required for correct localisation of the cleavage furrow during cytokinesis. The FAZ is also of wider interest because it is a novel structure with the potential to provide insights into how cells co-ordinate the spatial and temporal expression of proteins. Most studies of the FAZ have employed detergent-extraction techniques and have therefore focused on the cytoskeletal components of the FAZ. Little is known about the membrane proteins in the extracellular space between the flagellum and the cell body. These surface proteins are likely to play a key role in the physical attachment of the flagellum onto the cell body. In the procyclic form of the parasite, two membrane glycoproteins, FLA1 and FLA1BP, have been shown to mediate flagellar adhesion. However, the bloodstream-form FAZ is less well understood. Only a single membrane protein, FLA3, has been shown definitely to be essential for flagellar attachment in the bloodstream form, although others have been implicated. This thesis investigates further the localisation and function of FLA3. Additionally, another membrane glycoprotein, FLA2, is demonstrated here to be essential for flagellar attachment and cytokinesis in the bloodstream form. Multiple in-situ tagging approaches were employed to add a variety of epitope tags to the respective C-termini of FLA2 and FLA3, enabling localisation studies, interaction studies and preliminary investigations of the glycan side chains of the two proteins. Tagged FLA3 was shown to locate to the flagellar membrane of the FAZ. Super-resolution microscopy showed that the protein had a regularly spaced punctate distribution, consistent with the view that FLA3 is a component of the junctional complexes that span the intermembrane region of the FAZ, and which are critical for attachment of the flagellum to the cell body. Tagged FLA3 was able to bind both RCA-I lectin and tomato lectin, indicating that the glycoprotein possesses galactose residues and, probably, N-acetyllactosamine repeats. Specific knockdown of FLA2 by RNAi confirmed for the first time that FLA2 is essential for flagellar attachment and cytokinesis in the bloodstream form. Epitope tagging of FLA2 was achieved using a long-primer PCR method. The molecular weight of the mature protein suggested extensive post-translational modification. Tagged FLA2 was able to bind RCA-I lectin, indicating that the protein is glycosylated and possesses galactose residues. The protein was not observed to localise to the FAZ when tagged at the C-terminus with any of a variety of epitope tags. Rather, the tagged protein mislocalised throughout the cell. This mislocalisation precluded precise localisation studies and interaction studies. It is postulated here that in the bloodstream form, FLA2 performs the adhesion role previously attributed to FLA1. It is highly likely that interaction between FLA2 and FLA3 is required for flagellar attachment.
APPROVED
Keywords: trypanosome; Trypanosoma brucei; flagellum; FAZ; flagellar attachment zone; FLA2; FLA3; flagellum attachment zone; membrane glycoprotein; STED